THE CONCEPT OF TEACHER IN THE QUR`AN AND ITS RELEVANCE TO HIS FUNCTION IN THE DIGITAL ERA - Mujahidin, Anwar; Nursalam, Yufridal Fitri; Ju'subaidi, Ju'subaidi (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2021)
In today's digital technology era, teachers' function in the learning process seems obscure. They are only perceived as learning facilitators. This paper attempted to find relevant teacher's concepts in the digital era according to the interpretation of the Qur'an. The perspective of the Qur'an interpretation needs to be studied as a source of knowledge to find teacher's concepts relevant to the digital era because the existing studies on teachers tend to be based on partial perspective between theory and norm. It was conducted under the interpretation of the Qur'an on the development and internalization of science. The interpretation of some verses was analyzed for contextuality and its implications on the function of teachers in the current era. The study results suggested that a teacher should function as an educator and caregiver. He/she not only teaches science but also directs and nurtures students, so they understand and practice moral goodness. Education is responsible for developing not only cognitive but also psychomotor skills. It must also improve students' knowledge of goodness and virtue so that they can practice it in the end. That the function of a teacher is to educate and nurture students to be a good human is yet relevant today. This paper suggested a deeper research to examine the decline in the role of teachers around the school environment by evaluating the curriculum and learning system.